Aspirational Reflections: The Future of Sport History. Issue 5 (13th April 2017) - Dichter, Heather L.; Vamplew, Wray
Abstract: This article provides a scrambled form of SWOT analysis of the ideas contained in the various contributions to this special issue on sport historians and the field of sport history. The market for sport history, pure and simple, is not in good shape in many places. Yet we must be careful not to confuse trends in employment prospects with shorter term fluctuations in demand. Nor should we conflate national issues with the international situation. One thing is certain: worldwide academia is expanding; surely, there must be opportunities somewhere for sport history. Sport historians may have to be prepared to move geographically or to get a job. Nonetheless, the field of sport history also has many strengths highlighted, and opportunities abound for collaborations, public engagement, and supporting our fellow sport historians across the globe. Instead of allowing the external threats and weaknesses to continue to grow, sport historians should draw on the encouraging aspects contained herein and take advantage of our field's strengths and opportunities to develop new and creative initiatives which demonstrate the vibrancy and breadth of sport history.